The impact of partner framing on corporate image in ESG Publicity: focusing on the mediating effects of processing fluency and authenticity - Kim, Jaehyun; Hyun, Park Dong; Kim, Gwigon (Journal of Posthumanism, 2025)
This study empirically analyzed the impact of ESG Publicity based on partner participation on corporate image in ESG management. The purpose of this study is to investigate the impact of message framing methods that compose partner information based on partner framing (packing vs. unpacking) on processing fluency and authenticity, as well as corporate attitudes and corporate image. In addition, it was intended to confirm the mediating effect of processing fluency and authenticity, corporate attitude, and the moderating effect of E, S, and G activities. As a result of the study, it was confirmed that unpacking framing, which specifically lists partner information, is more effective in enhancing processing fluency and authenticity than packing framing. In addition, processing fluency and authenticity play a mediating role in the relationship between partner framing and corporate image, and have a positive effect on corporate image through corporate attitude. Although the moderating effect analysis of E, S, and G activities did not validate the moderating effect, eco-friendly activities (E) were found to have a greater impact on processing fluency and authenticity compared to social (S) and governance (G) activities. This study shows that presenting partner information in an unpacking framing method is key to enhancing corporate image when a company conducts ESG Publicity.